Validation of the Malay Version of Addenbrooke’s Cognitive Examination III in Detecting Mild Cognitive Impairment and Dementia - Kan, Kwai Ching; Subramaniam, Ponnusamy; Shahrizaila, Nortina; Kamaruzzaman, Shahrul Bahyah; Razali, Rosdinom; Ghazali, Shazli Ezzat (Karger Publishers Open Access, 2019)
Background/Aims: This study aimed to investigate the validity and reliability of the Malay version of Addenbrooke's Cognitive Examination III (ACE-III) for detecting mild cognitive impairment (MCI) and dementia. Methods: A total of 152 participants (dementia = 53, MCI = 38, controls = 61) were recruited from two teaching hospitals. The Malay version of ACE-III was translated following the standard guidelines for cross-cultural adaptation of measure. All the participants were assessed with the Malay version of ACE-III and Mini-Mental State Examination (MMSE). Results: The reliability of the Malay version of ACE-III was good with Cronbach's α coefficient of 0.829 and intraclass correlation coefficient of 0.959. There was a strong positive correlation between the Malay version of ACE-III and MMSE (r = 0.806). Age (r = -0.335) and years of education (r = 0.536) exerted a significant correlation with total score performance. The cutoff score to discriminate dementia from healthy controls was 74/75 (sensitivity = 90.6%, specificity = 82.0%) whereas to discriminate MCI, the cutoff score was 77/78 (sensitivity = 63.2%, specificity = 63.9%). The diagnostic accuracy of ACE-III was higher than that of MMSE in the detection of dementia (area under the curve: ACE-III = 0.929 vs. MMSE = 0.915). Conclusions: The Malay version of ACE-III demonstrated to be a reliable and valid screening tool for dementia. © 2019 The Author(s) Published by S. Karger AG, Basel.